The Integration of TeamSTEPPS Into Interprofessional Education Curricula at 3 Academic Health Centers. Issue 2 (June 2019) - Davis, Beth P.; Jernigan, Stephen D.; Wise, Holly H.
Abstract : Background and Purpose: The need for developing collaborative practice–ready health care providers, along with new interprofessional education (IPE) accreditation standards, highlights the importance of IPE in physical therapist education curriculum. As we strive to meet the goal of preparing students for collaborative practice and team-based care, the TeamSTEPPS system can be integrated into IPE programs to assist in the provision of quality health care and in the prevention of medical errors. Emory University (Emory), Kansas University Medical Center (KUMC), and the Medical University of South Carolina (MUSC) have integrated TeamSTEPPS into their IP classroom- and practice-based curricula. The purpose of this paper is to describe how these academic health centers have embedded TeamSTEPPS into their IP curricula, with the goal of assisting academic and clinical faculty with the development and implementation of learning activities directed toward the development of IP competency. Method/Model Description and Evaluation, Outcomes: The IPE models used by Emory, KUMC, and MUSC use the TeamSTEPPS framework and are described with select evaluation measures and outcomes. The Emory and KUMC models are primarily classroom based, whereas the MUSC uses a combined classroom- and clinic-based model. Although each institution's model for IP training and assessment is different, all have shown positive results. Discussion and Conclusion: With new IPE accreditation standards for most health professions programs, using TeamSTEPPS is a strategy to assist in meeting the standards for IPE training and a larger goal of improving the quality and safety of patient care. Abstract : Supplemental Digital Content is Available in the Text.